2019
DOI: 10.1101/643023
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Neurophysiological alterations in the nucleus reuniens of a mouse model of Alzheimer’s disease

Abstract: Key Points Alterations in the neurophysiology of hippocampal and cortical neurons has been linked to network hyperexcitability in mouse models of amyloidopathy.  The nucleus reuniens (Re) is part of a cognitive network involving the hippocampal formation and prefrontal cortex. Increased cellular activity in Re has been linked to the generation of hippocampal-thalamo-cortical seizure activity in J20 mice.  Re neurons display hyperpolarised resting membrane potentials in J20 mice. Passive membrane properties … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…It was suggested that pharmacological actions with agonists for vasopressin Avpr1b receptors in fi eld CA2 might potentially be useful for improving social memory in various types of dementia [Smith et al, 2016]. Studies have shown that pathological β-amyloid loading also alters neuron activity in the reuniens nucleus [Walsh et al, 2020], with the result that the connection of the hippocampus with the prefrontal cortex must be degraded.…”
mentioning
confidence: 99%
“…It was suggested that pharmacological actions with agonists for vasopressin Avpr1b receptors in fi eld CA2 might potentially be useful for improving social memory in various types of dementia [Smith et al, 2016]. Studies have shown that pathological β-amyloid loading also alters neuron activity in the reuniens nucleus [Walsh et al, 2020], with the result that the connection of the hippocampus with the prefrontal cortex must be degraded.…”
mentioning
confidence: 99%